STUDY ON WARM FORMING LIMIT PREDICTION OF ADVANCED HIGH STRENGTH STEEL DP780 SHEET METAL - WANG KaiDi; LI Di; LENG YangSong; FU QiuTao; XU JiaChuan; JIANG Ning (Jixie qiangdu)
In order to accurately predict the forming limit curve of DP780 steel sheet under the condition of warm forming,the ductile fracture prediction model was introduced into the numerical simulation. Based on the unidirectional tensile test results analysis of DP780 steel sheet in the temperature range of 573 K ～ 873 K and strain rate range of 6. 67×10-4 s-1～ 6. 67×10-3 s-1,the warm forming performance of DP780 steel sheet is better under the condition of temperature of 673 K and strain rate of3. 33×10-3 s-1 determined by the product of strength and ductility. And through the simple tensile test and simulation under this deformation condition,determined the main factors affecting the ductile fracture of DP780 steel sheet. Thus a model for predicting tensile fracture and shear fracture of DP780 steel under different strain paths was developed,by combining it with the warm forming constitutive model and the Hill ’48 yield criterion,the finite element simulation of the rigid mold bulging test was realized,and the forming limit curve of DP780 steel sheet at the temperature of 673 K was predicted,The mathematical model of forming limit was established. The results show that the forming limit results predicted by this method have better precision.